EFFECT EARNING ACTIVITY ON THE ATTITUDES TOWARDS SCIENCES OF STUDENT IN SECONDARY SCHOOL IN JAMBI CITY - Nur Ika Sandi Pratiwi; Astalini Astalini; Dwi Agus Kurniawan (PENA KREATIF : JURNAL PENDIDIKAN, 2022)
This study aims to determine whether there is an effect of student learning activeness on students' attitudes in science subjects in junior high schools in Jambi City. The research method used is a mixed research method with an explanatory design. The population in this study were all students of junior high school18 Jambi City, junior high 21 Jambi City, and students of junior high school 24 Jambi City. The number of samples used was 250 students. The research data were obtained by distributing a questionnaire on student learning and attitude questionnaires in science subjects, as well as conducting interviews with students. Furthermore, the data were analyzed quantitatively by type simple regression as well as with inferential statistics. The results showed that student learning activeness influenced attitudes in science subjects with a contribution of 15.2% influence while the remaining 84.8% was influenced by other factors not examined in this study, hereinafter referred to as intervening variables. Furthermore, from the calculation of the t-test values obtained t arithmetic greater than t table (20 299 1.650971), which means Ha (accepted) or there is an influence on the attitudes of students' learning activeness in science subjects. From the results of this effect, the regression equation is obtained, namely Y = 111.113 + 0.334x. So it can be concluded that if students have good learning activeness, then students will also show a good attitude in learning, especially in learning science.